Carbonaceous deposits on cobalt particles reverse the catalytic patterns in butadiene hydrogenation. Issue 4 (7th February 2023) - Chen, Zhibing; Guo, Luyao; Wang, Yi; Mou, Xiaoling; Chen, Zupeng; Lin, Ronghe; Ding, Yunjie
Abstract : The in situ formed carbonaceous deposits on a nitrogen-doped carbon-supported cobalt nanoparticle catalyst dramatically enhanced butenes selectivity and catalyst stability in butadiene hydrogenation. Abstract : We report the decisive roles of in situ formed carbonaceous deposits in dramatically reversing the performance of a cobalt nanoparticle catalyst in butadiene hydrogenation. A delicate balance between the deposition and removal of the carbonaceous deposits established on the pre-coked catalyst promotes highly selective and stable hydrogenation.